Agency Archaeology and Anthropology: foundations of agency in material culture studies - Diogo de Souza, Camila (2022)
The notion of agency has been used frequently in archeology for over thirty years now. During this period, the meanings and uses of the concept of agency were appropriated and transformed from the paradigms of the different archaeological interpretative views. However, these uses often lack theoretical discussions and clear didactic explanations about the origins, principles and models of the notion of agency. Recently, the concept of agency has been subjected to an increasingly intense theoretical and methodological review and debate in ​​material culture studies and has become a central point in the process of understanding past societies through relational study between people, materiality and fields of action. This article aims to present and discuss the development of the notion of agency, its foundations and parameters applied to the studies of material culture. We will explore the concept in the field of Anthropology in order to understand how its assumptions reached of Archeological Theory and provide some instruments and didactic tools for the adoption and applicability of the uses and meanings of the material agency.